PENGARUH MEDIA PEMBELAJARAN INTERAKTIF BERBASIS ADOBE FLASH TERHADAP HASIL BELAJAR SISWA MATERI EKOSISTEM KELAS X SMA NEGERI 1 SIANTAN - Khairiyah, Khuzmatul; Syamswisna, Syamswisna; Titin, Titin (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research aims to determine the effect of interactive learning media based on adobe flash of student learning outcomes on ecosystem material in class X SMA Negeri 1 Siantan. The form of this research is Quasi Experimental Design with Nonequivalent control group design. The study sample was class X MIA 1 (experimental class) and class X MIA 2 (control class). The sampling technique was used saturated sampling. The instrument used was multiple choice test consist of 20 items.The average learning outcomes of eksperimental class which the conclusion was 16,38 while the average in control class was 14,08. Based on Mann-Whitney U test results, obtained Zhitung (-4.04) <-Ztabel (-1.96), that was a significant difference between learning outcomes of studebts who taught by interactive learning media based on adobe flash adobe and student who taught by power point media.Value effect size obtained by 0.99 with high category, it shows that learning by interactive learning media based on adobe flash adobe gives effect of 33.89%. Keywords: Adobe Flash, Learning Outcomes, Ecosystem Material.